Biodegradable magnesium incorporated microspheres enable immunomodulation and spatiotemporal drug release for the treatment of osteonecrosis of the femoral head. (1st February 2023) - Yang, Fenghe; Xu, Chuanping; Zhang, Wei; Sun, Lei; Feng, Guiyu; Ning, Tianqin; Wang, Wei; Sun, Bingbing; Li, Jinyu; Niu, Xufeng; Fan, Yubo
Abstract: Osteonecrosis of the femoral head (ONFH) is a progressive disease that may lead to collapse of the femoral head and subsequently, progression to osteoarthritis of the hip. Although biomaterials have been widely used as carriers of active pharmaceutical ingredient for the treatment of early ONFH, current carriers are incapable of modulating the complex endogenous tissue healing process including osteogenesis, angiogenesis, and especially inflammation, which is the non-negligible step in bone repair. Herein, a kind of microspheres composed of magnesium (Mg), bone morphogenetic protein-2 (BMP-2) and poly(l -lactic acid) (PLLA) (Mg/BMP-2/PLLA microspheres) is developed as a novel drug delivery system to make up for the above shortcomings. In vitro studies show that BMP-2 release can be facilely manipulated by Mg contents, and a spatiotemporal release of Mg and BMP-2 is achieved. Cell-microspheres co-cultured experiments reveal that 2%Mg/BMP-2/PLLA microspheres possess the most pronounced effect on proliferation and osteogenic differentiation of MC3T3-E1 pre-osteoblasts. Furthermore, using a rabbit model of ONFH, 2%Mg/BMP-2/PLLA microspheres are proved with osteogenic, angiogenic and immunomodulatory effects which facilitate bone tissue regeneration. The developed Mg/BMP-2/PLLA microspheres with spatiotemporal release manner and immunomodulatory property hold great promise for improved treatment of early ONFH as well as other bone injury under pathological conditions. Graphical abstract: Image 1 Highlights: A kind of magnesium incorporated microspheres is developed for the treatment of osteonecrosis of the femoral head (ONFH). The composite microspheres enable immunomodulation and spatiotemporal drug release to cope with the bone healing process. The composite microspheres stimulate bone tissue formation and restore bone metabolism homeostasis at the osteonecrosis site. The composite microspheres hold great promise for improved treatment of early stage ONFH.